2004
DOI: 10.1016/j.orthres.2004.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical environment alters tissue formation patterns during fracture repair

Abstract: Fracture repair has previously been shown to be sensitive to mechanical environment, yet the specific relationship between strain character, magnitude and frequency, as well as other mechanical parameters, and tissue formation is not well understood. This study aimed to correlate strain distribution within the healing fracture gap with patterns of tissue formation using a rat model of a healing osteotomy subject to mechanical stimulation in bending. Finite element models based on realistic tissue distributions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 22 publications
1
41
0
1
Order By: Relevance
“…How bone struts sense the orientation of strains and then respond appropriately, however, remains unknown, although there is some indication from tissue engineering studies that the struts are particularly responsive to tensile strains (e.g. Smith-Adeline et al, 2002;Goldstein, 2004). Similarly, the radon transform approach used here does not enable us to distinguish the relative contributions of trabecular density and thickness to OPTD.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…How bone struts sense the orientation of strains and then respond appropriately, however, remains unknown, although there is some indication from tissue engineering studies that the struts are particularly responsive to tensile strains (e.g. Smith-Adeline et al, 2002;Goldstein, 2004). Similarly, the radon transform approach used here does not enable us to distinguish the relative contributions of trabecular density and thickness to OPTD.…”
Section: Discussionmentioning
confidence: 91%
“…Finally, a number of more clinically focused studies have examined the effect of pathologies and surgically based, tissue engineering approaches on trabecular architecture. In general, these studies find that the mechanical environment of a joint has considerable effects on mechanisms of tissue repair relevant to trabecular bone (Hollister et al, 2001;Smith-Adeline et al, 2002;Goldstein, 2004;Papaloucas et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Forces arising from muscle contraction, contact at joint surfaces and different growth rates in adjacent tissues produce a variety of local mechanical stimuli in skeletal tissues, including pressures, strains and fluid flow. Using the concept that specific combinations of these stimuli regulate the differentiation of multipotent mesenchymal tissue, previous studies have investigated the mechanobiology of fibrocartilaginous metaplasia (Giori et al, 1993;Wren et al, 1998), implant integration (Prendergast et al, 1997), the development of pseudarthroses (Loboa et al, 2001), fracture healing (Blenman et al, 1989;Carter et al, 1998;Claes and Heigele, 1999;Gardner et al, 2004Gardner et al, ,2000Lacroix and Prendergast, 2002;Smith-Adaline et al, 2004) and distraction osteogenesis Loboa et al, in press). Results from these studies suggest the possibility of using the physical environment as a factor that can be controlled in order to promote a specific healing or development outcome.…”
Section: Introductionmentioning
confidence: 99%
“…34 Uniaxial tensile strain has been used as another mode of mechanical stimulation to successfully induce bone regeneration in vivo via distraction osteogenesis. [57][58][59][60][61][62] Buchman et al developed a rat model establishing specific parameters, including critical bone defect size as greater than 3 mm to sufficiently study the mechanisms of distraction osteogenesis and provide a quantitative distinction from conventional bone fracture healing. 59 Following this work, in an in vivo study utilizing rat models, Loboa et al 63 reported that gradual distraction of the hemi-mandible (0.25 mm every 12 h) over 8 days, followed by 28 days of rest resulted in periosteal bone formation by postoperative day 7 and a full bridge of new bone spanning the width of the distraction gap by postoperative day 41.…”
Section: Figmentioning
confidence: 99%